Avidity‐driven polarity establishment via multivalent lipid–GTPase module interactions. (17th December 2018) - Meca, Julien; Massoni‐Laporte, Aurélie; Martinez, Denis; Sartorel, Elodie; Loquet, Antoine; Habenstein, Birgit; McCusker, Derek
Abstract: While Rho GTPases are indispensible regulators of cellular polarity, the mechanisms underlying their anisotropic activation at membranes have been elusive. Using the budding yeast Cdc42 GTPase module, which includes a guanine nucleotide exchange factor (GEF) Cdc24 and the scaffold Bem1, we find that avidity generated via multivalent anionic lipid interactions is a critical mechanistic constituent of polarity establishment. We identify basic cluster (BC) motifs in Bem1 that drive the interaction of the scaffold–GEF complex with anionic lipids at the cell pole. This interaction appears to influence lipid acyl chain ordering, thus regulating membrane rigidity and feedback between Cdc42 and the membrane environment. Sequential mutation of the Bem1 BC motifs, PX domain, and the PH domain of Cdc24 lead to a progressive loss of cellular polarity stemming from defective Cdc42 nanoclustering on the plasma membrane and perturbed signaling. Our work demonstrates the importance of avidity via multivalent anionic lipid interactions in the spatial control of GTPase activation. Synopsis: While Rho‐family GTPases play a critical role in generating cell polarity at the plasma membrane of eukaryotes, the mechanisms underlying their anisotropic activation are incompletely understood. This study identifies a mechanism of anisotropic Cdc42 activation in budding yeast via targeting of the scaffold protein Bem1 and the associated GEF Cdc24 to anionic lipids. Bem1 and Cdc24 cannot be targeted to the cell pole in cells lacking phosphatidyserine and phosphoinositides. Bem1 targeting required N‐terminal clusters of basic residues that mediate robust interactions with anionic lipids. Bem1 recruitment to anionic lipids influenced membrane rigidity in an ergosterol‐dependent manner. The interaction of Bem1 with anionic lipids is required for limiting Cdc42 diffusion at the cell pole and for promoting its nano‐clustering. Multivalent lipid binding sites in Bem1 and Cdc24 are required for the avid targeting of the complex to the cell pole and for normal cellular polarity. Abstract : Quantitative in vivo imaging and reconstitution experiments identify a mechanism by which Cdc42‐mediated cell polarity is established in budding yeast.